A Gold–Palladium Nanoparticle Alloy Catalyst for CO Production from CO2 Electroreduction. Issue 4 (1st April 2019) - Bellini, Marco; Folliero, Maria G.; Evangelisti, Claudio; He, Qinggang; Hu, Yongfeng; Pagliaro, Maria V.; Oberhauser, Werner; Marchionni, Andrea; Filippi, Jonathan; Miller, Hamish A.; Vizza, Francesco
Abstract : Electrochemical CO2 reduction reaction (CO2 RR) is a promising technology for combining CO2 reutilization and renewable electricity storage. For economic feasibility, better catalysts are required to overcome current limitations such as high overpotentials, poor faradaic efficiencies (FEs), and low current densities. Herein, size‐ and composition‐controlled gold (Au)–palladium (Pd) bimetallic alloy nanoparticles prepared by a metal vapor synthesis technique together with the monometallic Au and Pd equivalent materials are investigated. X‐ray diffraction and high‐angle annular dark‐field scanning transmission electron microscopy energy‐dispersive X‐ray spectroscopy analyses confirm the Au–Pd alloy formation with an average atomic ratio of 76 Pd wt% and 24 Au wt%. These bimetallic and the monometallic catalysts are characterized and tested for the electroreduction of CO2 in electrochemical cells and also in a complete CO2 electrolysis cell. Analysis of the reduction products shows a 100% CO2 RR selectivity for CO. The FE for CO with respect to H2 as high as 90% is obtained with Au–Pd/C by tuning the electrode structure. The Au/C and Pd/C catalysts also show a better selectivity for CO with no evidence of other CO2 RR products. The Au–Pd alloy formation improves the FE of Pd for CO by suppressing the parasitic H2 evolution reaction. Abstract : An electrochemical technology for the transformation of CO2 into fuels needs catalysts with better selectivity. Herein, size‐ and composition‐controlled gold (Au)–palladium (Pd) alloy nanoparticles are prepared by metal vapor synthesis. This study shows that the Au–Pd alloy formation improves the faradaic efficiency of Pd for CO by suppressing a parasitic H2 evolution reaction.